The profile of child malnutrition in Imbabura and the role of public policies: The profile of child malnutrition in Imbabura (La U Investiga, 2021)
Child malnutrition limits the progress of societies and despite the notable reductions in its prevalences over time, Ecuador has a critical situation for its level of development. The objective of the research is to characterize child malnutrition in Imbabura, its progress over time and the role of public policies. The methodology is mixed, with quantitative methods of the probabilistic model with pooling data and qualitative methods of documentary review, using the 1999, 2006 and 2014 Living Conditions Surveys, and the development and land use planning, respectively. Among the main results is that Imbabura has achieved a reduction higher than the national average, with different prevalence among population groups.